Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis Overlay Associated with Self-Medication of Sulfadoxine-Pyrimethamine Overdose in a Patient with HIV/AIDS Infection: A Case Report - Jalloh A; Abiri OT; Jalloh IIT; Thomas F; Conteh Jnr TA; Forde MYE; Sesay M; Komeh JP (International Medical Case Reports Journal, 2025)
Abdulai Jalloh,1 Onome T Abiri,2,3 Ishmael IT Jalloh,2 Fawzi Thomas,3,4 Thomas Ansumus Conteh Jnr,3,4 Martha YE Forde,1 Mohamed Sesay,3 James P Komeh3 1Department of Surgery, Faculty of Clinical Sciences, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 2Department of Pharmacology and Therapeutics, Faculty of Basic Medical Sciences, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 3National Pharmacovigilance Centre, Pharmacy Board of Sierra Leone, Freetown, Sierra Leone; 4Department of Pharmaceutics, Faculty of Pharmaceutical Sciences, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra LeoneCorrespondence: Onome T Abiri, Department of Pharmacology and Therapeutics, Faculty of Basic Medical Sciences, College of Medicine and Allied Health Sciences University of Sierra Leone, Freetown, Sierra Leone, Tel +23276370315, Email berylonome@gmail.comAbstract: Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) overlap is a severe delayed-type hypersensitivity reaction causing widespread blistering and necrosis of skin and mucosa. Sulfadoxine-pyrimethamine (SP) and HIV/AIDS infection are associated with hypersensitivity reactions, including SJS and TEN. A 20-year-old female with HIV/AIDS presented with fever, body pain, and skin blisters on her face, neck, trunk, and perineum. She was non-compliant with antiretroviral therapy. The lesions developed three days after self-administering SP for malaria, taken as two tablets every 12 hours for three days. The skin involvement was 23% of total body surface area (TBSA). The Naranjo Adverse Drug Reaction Scale Score of four suggested a possible association between SP and SJS/TEN overlap, considering HIV/AIDS can precipitate this reaction. The severity-of-illness score of toxic epidermal necrolysis (SCORTEN) score was one, with predicted mortality of 3.2%. The patient received conservative treatment including fluids, antimicrobials, nutrition, and wound care, leading to complete recovery. It is imperative that the medicine regulatory authority and healthcare professionals educate HIV patients to avoid self-medication with antibiotics such as SP due to the increased risk of serious adverse drug reactions, including SJS/TEN.Keywords: Stevens-Johnson syndrome, toxic epidermal necrolysis, hypersensitivity, Sulfadoxine-pyrimethamine, HIV/AIDS infection, case report